ANALISIS PENGARUH KUALITAS WEBSITE PERPUSTAKAAN UNIVERSITAS SEPULUH NOPEMBER PAPUA - Astrin Aprilia Umasugi; Emy L. Tatuhey (ADISAM PUBLISHER, 2026)
This research aims to analyze the influence of library website quality on user satisfaction at Sepuluh Nopember Papua University. In the digital era, libraries no longer function solely as repositories of physical collections but also as integrated knowledge centers with digital services. The library website has become an essential component determining the level of accessibility and user satisfaction with library services. This study implements the End-User Computing Satisfaction (EUCS) method with five measurement dimensions: content, accuracy, format, ease of use, and timeliness. The research involved 107 respondents consisting of 85 students, 21 lecturers, and 1 library operator. Data was collected through questionnaires using a 5-point Likert scale and analyzed using quantitative methods. Validity test results indicate that all question items are valid with r-calculated values > r-table (0.191). Meanwhile, the reliability test yielded a Cronbach's Alpha value of 0.91, demonstrating excellent internal consistency. Based on the analysis results, the accuracy dimension received the highest score with a total score of 445 out of a maximum value of 500, followed by format, ease of use, content, and timeliness dimensions. This research provides a comprehensive overview of the USN PAPUA library website quality and is expected to serve as a foundation for administrators in improving digital library services to meet user expectations and optimize the utilization of library resources in the digital era